The outcome of ureterocele management at Queen Sirikit National Institute of Child Health - Jitkarnka, Uttasit; Tonvichien, Lantom (Insight Urology, 2005)
Objective: To evaluate the result of surgical management of ureterocele by various techniques at Queen Sirikit National Institute of Child Health. Material and methods: The records of all children with ureterocele who underwent surgery at Queen Sirikit National Institute of Child Health between 1999 to 2003 were reviewed. Age, sex, number of renal system, presenting symptoms, imaging, and operative techniques were analysed. Results: There were 25 cases (26 renal units), 19 girls and 6 boys .Five cases (25%),6 renal units, had single system which one boy had bilateral ureterocele and 20 cases (75%)were duplex system. Mean age at first operation was 24.9 months (range between 11 days to 6 years), 14 cases were under 12 months. Presenting symptom were recurrent UTI (92%), abnor- mal urination (16%), abnormal mass (12%), failure to thrive (8%), prolapsed ureterocele (4%), abdominal pain (4%) and antenatal hydronephrosis (4%). Patients were divided into 3 groups according to types of surgery. Group A, 15 cases (60%) underwent transurethral incision (TUI), 4 cases were success after first TUI, 3 cases needed second TUI and another 8 cases needed second operations; 7 excision of ureterocele and reimplantation and 1 nephrectomy due to nonfunction single system. The mean time between the first and second operation was 12 months (range 3-26 months). Group B, 7 cases underwent upper pole heminephrectomy alone and 1 needed excision of ureterocele and common sheath reimplantation due to high grade reflux of the lower moiety ureter. Group C, 2 cases underwent excision of ureterocele and reimplantation in which one boy had bilateral single system and another one was duplex and high grade reflux of both system. Conclusion: Transurethral incision of ureterocele is the treatment of choice for decom- pression of the obstructed hydroureters in both single or duplex system, especially for infancy and younger child and had 47% (7/15) success rate by TUI alone in this study. The second operation is needed in complicated cases especially who has multiple lower tract anomalies.